The Influence of Athanasius and the Homoiousians on Basil of Caesarea's Decentralization of "Unbegotten" - DelCogliano, Mark (Journal of early Christian studies, 2011)
A tradition of argumentation against the name "Unbegotten" and in favor of "Father" can be detected in Athanasius, in the Homoiousians Basil of Ancyra and George of Laodicea, and in Basil of Caesarea. This study articulates a methodology for exploring the complex manner in which Athanasian thought was adopted by Basil of Caesarea through the intermediary of the Homoiousians by examining how each formulated this argument for the decentralization of "Unbegotten" and how the Homoiousians and Basil of Caesarea used and modified the arguments of their predecessors. It is demonstrated that Basil of Caesarea appropriated this argument in its homoiousian rather than its Athanasian form.